Singularities of the structure of two-sided ideals of a domain of elementary divisors - Bilyavs’ka, S. I.; Zabavskii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We prove that, in a domain of elementary divisors, the intersection of all nontrivial two-sided ideals is equal to zero. We also show that a Bézout domain with finitely many two-sided ideals is a domain of elementary divisors if and only if it is a 2-simple Bézout domain.